Accuracy of Multi-Detector Computed Tomography In the Diagnoses of Adnexal Masses (KYAMC Journal, 2023)
Background: Ovarian cancer is the 5th common cause of death in women. patients older than 30 years are high malignant potential group. The lifetime risk of dying from invasive ovarian cancer is about 1 in 95. Modern imaging techniques have demonstrated significant accuracy in the diagnosis and staging of adnexal masses that help the clinician in surgical and post-surgical treatment planning. Objective: To determine the accuracy of multidetector computed tomography (MDCT) in diagnoses of benign and malignant adnexal masses, compare it with histopathological diagnoses and find out the sensitivity, specificity, positive predictive value, negative predictive value of MDCT in diagnoses of benign and malignant adnexal masses. Materials and Methods: This cross-sectional observational study was carried out between January 2013 to December 2014 with 45 patients referred for an MDCT scan of the pelvic organ with a suspicion of adnexal mass in Dhaka Medical College, Dhaka. All the patients were evaluated by detailed history and clinical examination. CT scan of the pelvic organ was performed in all cases and the report was checked by the radiologists of DMCH. Operated patients were followed up after surgery up to histopathological diagnosis and correlated with CT scan findings. Results: CT diagnosis for evaluation of benign adnexal mass, sensitivity was 90.0%, specificity 92.0%, accuracy 91.1%, PPV was 90.0% and NPV 92.0%. In the case of malignant mass, sensitivity is 92.0%, specificity 90.0%, accuracy 91.1%, PPV 92.0% and NPV 90.0%. Conclusion: MDCT is a valuable modality in the diagnosis of benign and malignant adnexal masses.KYAMC Journal Vol. 14, No. 02, July 2023: 74-78.